PENGARUH EKSPOR IMPOR TERHADAP CADANGAN DEVISA DI INDONESIA - Cut Nova Rianda (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2020)
This study aims to analyze the amount of foreign exchange reserve in Indonesia. And the effect of exsports and imports on foreign exchange reserve in Indonesia. This data usade are secondary data derived from TheCentral Statistics Agency and Indonesian Banks. This research uses a quantitative analysis. Analysis to see whether the exsport and import factors significantly affect the foreign exchanges reserves in indonesia. Based on the regresion result in the know that exports have a positive and significant impact on Indonesian,s foreign exchange reserve while imports have a negative and significant impact on indonesian,s foreign exchange reserve.